Rural Women's Role in Economic Development: Case Study of Teluk Awur Village - Widyawati, Marta (Proceedings International Conference of Culture and Sustainable Development; Vol 1 (2023): PROCEEDINGS ICOCAS, 2023)
Women have a significant role in economic growth and social progress, especially in developing countries. This qualitative research examines the contribution of women in Teluk Awur village to local economic development using a gender approach. As a region that is economically transitioning due to the instability of the furniture industry and its tourist destinations, the progress of Teluk Awur cannot be successful without the role of women. Women can carry out financial management at the domestic and public levels. Most do not pursue higher education but are adaptable to survive amid uncertainty. Women have taken the initiative to manage the economy even in critical situations. The potential of these women needs to be further optimized by stakeholders so that they can support the development of the local tourism sector and increase economic welfare